2018
DOI: 10.1007/s10530-018-1770-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of data precision on the effectiveness of alien plant control programmes: a case study from a protected area

Abstract: Successful long-term invasive alien plant control programmes rely on alien plant distribution and abundance data to assess, prioritise, implement and monitor the efficacy of the programme. Here we assess the impact of data accuracy using the alien plant programme in Table Mountain National Park, South Africa. A systematic plot-based survey method was carried out to assess the distribution of alien plants in the park at a fine scale (systematic sampling). Alien plant richness, total area invaded and the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…In this study, formal sampling techniques were applied for data collection on nonnative species. Although systematic sampling will produce the best possible data set (Cheney et al 2018), this is, however, not the only approach for data collection. With training and experience, protected area staff can conduct field surveys to register the occurrence of non-native species with a GPS, while noting down invasion stage and frequency, as well as inferring invasion risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, formal sampling techniques were applied for data collection on nonnative species. Although systematic sampling will produce the best possible data set (Cheney et al 2018), this is, however, not the only approach for data collection. With training and experience, protected area staff can conduct field surveys to register the occurrence of non-native species with a GPS, while noting down invasion stage and frequency, as well as inferring invasion risk.…”
Section: Discussionmentioning
confidence: 99%
“…Information from other references is useful to corroborate these assumptions, as mentioned before. Cheney et al (2018) demonstrated how mistaken general perceptions can be, as there was substantive disagreement between datasets produced by managers and by systematic sampling, implying that field data has to be collected locally. The application of our scheme entails full cover of protected areas, or of entire sections in the case of former prioritization of sites for control, very large areas, or very limited financial resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These assumptions include that effective and professional clearing would continue into the future; that co-financing would be available; that due compensation for the services rendered and the value-added products produced would be realised; that the extent of the invasions was accurately known; and that the costs had been accurately estimated. Most, or even all, of the above assumptions will not hold, however, because alien plant invasions are rarely accurately mapped (see, for example, Cheney et al 2018); the costs of control are routinely under-estimated by a factor of 3-7 times; there are low levels of efficiency associated with control work; and including value-added products could lead to unintended consequences. Consequently, there can only be a low level of confidence in these predictions of the return on investment from control projects.…”
Section: Returns On Investment From Control Measuresmentioning
confidence: 99%